Sovereignty : a contribution to the theory of public and international law - Heller, Hermann, 1891-1933; Dyzenhaus, David (Oxford : Oxford University Press, 2019)
In this 1927 work, Hermann Heller addresses the paradox of sovereignty, with a discussion spanning the disciplines of history, constitutional and political theory, and international law. The book includes a substantial introductory essay by David Dyzenhaus.
Previously issued in print: 2019.
Includes index.
Specialized.
Description based on online resource; title from home page (viewed on May 7, 2019).
Keywords: Sovereignty